2009
DOI: 10.1063/1.3068500
|View full text |Cite
|
Sign up to set email alerts
|

Phase identification of self-forming Cu–Mn based diffusion barriers on p-SiOC:H and SiO2 dielectrics using x-ray absorption fine structure

Abstract: X-ray absorption fine structure spectroscopy has been used to study the chemical and structural properties of self-forming diffusion barrier layers from Cu-8 at. % Mn alloy films on porous low-k and thermally grown SiO2 dielectrics. For the porous low-k/Cu(Mn) system, we provide evidence that the interface is composed of MnSiO3 and MnO with near complete Mn segregation from the alloy film; however, we find that the self-forming process does not go to full completion on thermally grown SiO2 substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…1 and 2, the MnO x layer contains more carbon, suggesting more Si-C bonds, at 400 • C than at 200 • C. Additional possibility may be related to graded chemical composition in the MnO x layer. In the case of thermal reaction between Mn in Cu-Mn alloys and SiO 2 , the complex formation of MnO and MnSiO 3 was reported [11], [24]. The chemical composition of the complex formation was not an equilibrium constant value but was continuously graded across the layer.…”
Section: B Valence States Of Si and Mn In The Mno X Layermentioning
confidence: 95%
“…1 and 2, the MnO x layer contains more carbon, suggesting more Si-C bonds, at 400 • C than at 200 • C. Additional possibility may be related to graded chemical composition in the MnO x layer. In the case of thermal reaction between Mn in Cu-Mn alloys and SiO 2 , the complex formation of MnO and MnSiO 3 was reported [11], [24]. The chemical composition of the complex formation was not an equilibrium constant value but was continuously graded across the layer.…”
Section: B Valence States Of Si and Mn In The Mno X Layermentioning
confidence: 95%
“…The process involves the deposition of a Cu/metal alloy directly onto the dielectric, which upon anneal results in the expulsion of the alloying element to the dielectric interface where it chemically reacts to form a diffusion barrier. Mn, 5,6 Ti, 7 and Al 8 have been shown to be suitable alloying elements and to be effective at preventing Cu diffusion into the dielectric material.…”
mentioning
confidence: 99%
“…This may be the reason for the sparse and somewhat contradictory information found in the literature regarding the exact nature and composition of these barriers. 5,6,13 Scanning transmission electron microscopy in high angle annular dark field mode (STEM-HAADF) is a powerful technique based on the fact that the contrasts in the images are proportional to the atomic number of the species present. Therefore, it allows for the direct visualization of composition variation as a result of phase transformations or chemical reactions that could take place, which is not possible with conventional TEM.…”
mentioning
confidence: 99%
“…15 Manganese silicate (MnSiO 3 ) barrier layers have been the subject of considerable study due to their reported effectiveness as a barrier to Cu migration and improved Cu adhesion properties compared to other barrier layer candidates. 5,6,16,17 While the majority of studies to date have focused on the formation of MnSiO 3 barrier layers on SiO 2 surfaces, 6,18,19 the growth of the Mn based barrier layers on carbon containing ultra-low dielectric constant (ULK) materials has also been the subject of interest. 7,16,[20][21][22] The formation of effective barrier layers on these surfaces is essential if they are to be adopted by the industry.…”
Section: Introductionmentioning
confidence: 99%